The Legal Protection for Customers Using Online Loan Services - Irene Puteri A. S. Sinaga (Jurnal Daulat Hukum, 2022)
Currently, financial technology (fintech) is developing rapidly in Indonesia. The number of available fintech operating companies is increasing. The role of the Financial Services Authority is very important in supervising fintech-based companies in Indonesia in accordance with their authority in the field of financial services in general. The functions and authorities of the Financial Services Authority (in Bahasa “OJK”) are contained in Articles 4 and 5 of the Financial Services Authority Law with the aim of protecting consumers from all activities in the financial sector. This is also stated in Act No. 8 of 1999 concerning Consumer Protection (Consumer Protection Law) specifically in the field of Financial Services Products. Other rules regarding fintech supervision are contained in the Financial Services Authority Regulation Number 77/POJK. 01/2016 concerning Information Technology-Based Lending and Borrowing Services. The problem discussed is how is legal protection for customers in online loan agreements? What are the steps taken by the government to protect the rights of consumers who use illegal online loan services? The research method used is a normative juridical approach. Sources and types of research data collected by library studies include primary data, secondary data and tertiary data after being analyzed qualitatively. As of the time of writing, the regulations regarding OJK supervision of fintech-based companies are still minimal, so the importance of consumer protection in Indonesian law enforcement because there are still complaints from people in Indonesia in using online loan services. As of the time of writing, the regulations regarding OJK supervision of fintech-based companies are still minimal, so the importance of consumer protection in Indonesian law enforcement because there are still complaints from customer in Indonesia in using online loan services. Therefore, the importance of the involvement of the Financial Services Authority in providing guarantees of legal protection for the public, especially customers who use online-based lending and borrowing services.